The effect of octreotide on portal vein and peritoneal fluid cytokine levels in postoperative adhesion prevention - (:unkn) unknown (Turkiye Klinikleri, 2006)
Objective: The aim of this study is to investigate the effect of octreotide on portal vein and peritoneal fluid TNF-α and IL-6 levels in the postoperative adhesion formation. Material and Methods: Following an "adhesion model operation", 10 rats were given octreotide subcutaneously (25 μg/kg/day) for 10 days (study group) while other 10 rats did not receive any treatment (control group). Ten rats had only a midline laparotomy as sham. Adhesion scores, portal vein and peritoneal fluid cytokine levels were determined on the postoperative 10th day. Results: Octreotide significantly reduced the total adhesion score. It has also reduced the portal vein IL-6 and TNF-α (147 ± 2 pg/mL; 146.7 ± 2.6 pg/mL respectively) levels as compared to those of control group (193.5 ± 10 pg/mL; 195.8 ± 11.2 pg/mL respectively). There was no reduction (IL-6 132; 143 and TNF-α 132.8; 143.7) on contrary, elevations in peritoneal fluid cytokine levels, comparing to control. Conclusion: Octreotide reduces postoperative intraabdominal adhesion formation through the mechanisms those mediated by intestinal rather than peritoneal cytokine production. Copyright © 2006 by Türkiye Klinikleri.
Keywords: Adhesion; Cytokine; Octreotide